2008
DOI: 10.1183/09059180.00011004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatments for tobacco dependence

Abstract: There are currently three licensed therapies for smoking cessation: nicotine replacement (NR), bupropion and varenicline.NR can be indicated for: 1) aid in abrupt cessation; 2) gradual reduction in order to quit smoking; 3) temporary abstinence; and 4) smoking reduction maintenance. A meta-analysis has found that the relative risk of abstinence for any form of NR relative to control was 1.6. It has been found that starting NR treatment 1-3 weeks before smoking cessation and combining NR products, usually patch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…This should elicit a response and open discussion regarding the dangers of continuing cigarette smoking. Referral to support groups, educational and counselling sessions, and the use of newer pharmaceuticals all offer avenues for success [8,9,20,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This should elicit a response and open discussion regarding the dangers of continuing cigarette smoking. Referral to support groups, educational and counselling sessions, and the use of newer pharmaceuticals all offer avenues for success [8,9,20,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing cigarette taxes, reducing locations where smoking is allowed, litigating, advertising the effects of tobacco smoking and increasing the stigma of smoking have all been helpful [6,7]. Health practitioners have assisted their patients by listening, counselling, referring to support groups and prescribing drugs to mollify withdrawal effects from nicotine [8][9][10]. However, spirometry has usually been of minimal benefit [11][12][13], perhaps because results are not presented optimally.…”
mentioning
confidence: 99%
“…The most common indication for NRT is to aid the patients in abrupt cessation, but additional uses are also licensed in some countries, such as gradual reduction to quit; temporary abstinence, that is, for short periods of abstinence where smoking is not allowed; and maintenance of reduction [ 12 ]. NRT has also been investigated as an aid in reduction of habit size of nicotine use among smokers not willing to quit.…”
Section: Nicotine Replacement Therapy (Nrt)mentioning
confidence: 99%
“…NRT has also been investigated as an aid in reduction of habit size of nicotine use among smokers not willing to quit. In 2 meta-analyses, it was found that for smokers who are unwilling to stop smoking completely but want to reduce their habit size the use of NR compared with placebo increased the likelihood that they would make a cessation attempt and that they succeeded more often with the cessation [ 4 , 12 ].…”
Section: Nicotine Replacement Therapy (Nrt)mentioning
confidence: 99%
“…In the third chapter, CORNUZ and WILLI [3] describe nonpharmacological smoking cessation interventions in clinical practice, such as specific counselling to inform and sensitise the smoker and to motivate and support them to quit smoking. The next chapter deals with the specific pharmacological treatments to help in smoking cessation, and in this chapter FAGERSTRÖ M and JIMÉ NEZ-RUIZ [4] describe the role of nicotine replacement therapy on the one hand, and of bupropion and varenicline on the other. In the fifth chapter, WEST and STAPLETON [5] describe the clinical and public health significance of treatments to aid smoking cessation, and in the final chapter the implications and priorities for tobacco control in Belgium and Europe are discussed by BARTSCH [6].…”
Section: Introductionmentioning
confidence: 99%